The Impact of the Tourism Industry in Kosovo and Albania - RAMAJ-DESKU, Behrije; UKAJ, Fatos (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020, 2020)
Tourism is considered an industry with a high impact on the economic development of a country. Based on this fact, the main purpose of this paper is to present and compare the statistics of foreign and domestic visitors, as well as the impact of tourism to employment and GDP in Albania and in Kosovo. According to the summary statistics, there is a positive increase in the number of foreign and domestic visitors who have visited Kosovo. In Kosovo there is a less tourism contribution to employment and GDP than in Albania as tourism is more developed in Albania. Pristina is considered the most interesting city to visit by foreigners and locals. In Albania, the direct contribution of tourism to GDP in 2016, which was 8.4%, is projected to increase to 10% in 2022. The contribution of tourism to total employment in Albania in 2016 was 7.7%